2010
DOI: 10.1111/j.1365-2141.2009.08035.x
|View full text |Cite
|
Sign up to set email alerts
|

KIT mutations confer a distinct gene expression signature in core binding factor leukaemia

Abstract: Summary Core binding factor (CBF) leukaemias, characterized by either inv(16)(p13.1q22) or t(8;21)(q22;q22), constitute acute myeloid leukaemia (AML) subgroups with favourable prognosis. However, 40–50% of patients relapse, emphasizing the need for risk‐adapted treatment approaches. In this regard, studying secondary genetic aberrations, such as mutations of the KIT gene, is of great interest, particularly as they can be targeted by receptor tyrosine kinase inhibitors (TKI). However, so far little is known abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 51 publications
(63 reference statements)
2
32
1
Order By: Relevance
“…24 Similarly, the identification of KIT wild-type core-binding factor AMLs harboring expression profiles similar to KIT-mutated core-binding factors suggests that different leukemogenic events can result in the activation and deregulation of identical sets of genes and/or oncogenic pathways. 25 In accordance, gene expression signatures have been identified that reflect the heterogeneous clinical response of both CN-AML and core-binding factor AML, thereby providing further evidence that GEP-based outcome prediction in AML is feasible and can provide information in addition to cytogenetics and molecular genetics. 22,26 To discover gene expression signatures of prognostic value, a recent proof-of-principle study successfully applied a novel strategy including a combination of supervised and unsupervised data analysis and defined a 133-gene signature.…”
Section: Gep In Adult Amlmentioning
confidence: 70%
“…24 Similarly, the identification of KIT wild-type core-binding factor AMLs harboring expression profiles similar to KIT-mutated core-binding factors suggests that different leukemogenic events can result in the activation and deregulation of identical sets of genes and/or oncogenic pathways. 25 In accordance, gene expression signatures have been identified that reflect the heterogeneous clinical response of both CN-AML and core-binding factor AML, thereby providing further evidence that GEP-based outcome prediction in AML is feasible and can provide information in addition to cytogenetics and molecular genetics. 22,26 To discover gene expression signatures of prognostic value, a recent proof-of-principle study successfully applied a novel strategy including a combination of supervised and unsupervised data analysis and defined a 133-gene signature.…”
Section: Gep In Adult Amlmentioning
confidence: 70%
“…Recently, Luck et al, showed that KIT mutations confer a distinct gene expression signature in CBF-AML and that one of the most significantly differentially expressed gene is LRP6 that is essential for noncanonical WNT5A signaling and thus for the maintenance of stem and progenitor cells [43,44]. Authors suggested that the different gene profiling may lead to an enhancement of proliferation in the KITmutated cases, which may be reflected in the higher blast counts of those patients [43]. The clinical observations that affected patients with t(8;21) appear to have a higher WBC count and WBC-index at presentation and a higher frequency of EML might support this hypotheses [30,39,45].…”
Section: Discussionmentioning
confidence: 99%
“…25 BRB Array Tools Version 4.2.1 was also used for data analysis using class comparison and pathway class comparison tools as previously described. 26 All tests were two-sided. An effect was considered significant if the p values were 0.05 or less.…”
Section: Caspase Activity Assaymentioning
confidence: 99%